Phosphorous remediation using alginate/glomalin biobeads: Examining structural cohesivity, nutrient retention, and reapplication viability - Percivall, Kelly; Amgain, Naba R.; Inglett, Kanika; Strauss, Sarah L.; Bhadha, Jehangir H. (Frontiers in Environmental Science, 2022)
Excess nutrient loading from agriculture and urban runoff into limnetic and marine ecosystems is associated with harmful algal blooms that result in eutrophication. Sequestration of nutrients such as phosphorus (P) and nitrogen (N) from agricultural outflows and recycling them as soil amendments would be an environmentally and economically sustainable strategy to alleviate this problem. This study explored the use of biobeads constructed with phytoplankton, Chlorella vulgaris, alginate and glomalin as a possible medium for a cyclic culture-harvest-reapply (CHR) system to address the problem of eutrophication. These “biobeads” were constructed from different concentrations of sodium alginate, C. vulgaris, and glomalin. Bead vitality was evaluated by introducing C. vulgaris to both eutrophic (phosphate ~1.5 ppm) and hypereutrophic (phosphate ~ 4.0 ppm) solutions and measuring phosphate removal. After 9 days in the eutrophic solution, biologically active groups reduced orthophosphate concentrations by an average of 1.35 ppm (80%). In the hypereutrophic solution, an average of 1.52 ppm total phosphate removal (38%) was observed over five weeks. The addition of glomalin in high concentrations increased the structural cohesivity of the hydrogel matrix, while low concentrations had an inverse effect. Reapplication of these biobeads to topsoil did not reduce plant growth or plant health parameters. These data suggest that glomalin, in appropriate proportions, is a suitable secondary scaffolding for a sodium alginate hydrogel immobilization medium. The alginate beads of immobilized C. vulgaris could be a promising treatment technique for phosphorus-containing urban wastewater. Further research is warranted to assess long-term impacts on nutrient dispersal and soil quality upon reapplication.